Comprehensive Transcriptome Analysis of Stem-Differentiating Xylem Upon Compression Stress in Cunninghamia Lanceolata - Zhang, Zekun; Wang, Huiyuan; Wu, Ji; Jin, Yandong; Xiao, Shengwu; Li, Tao; Liu, Xuqinq; Zhang, Hangxiao; Zhang, Zeyu; Su, Jun; Liu, Jingzao; Wang, Xiaoyan; et al. (Frontiers in Genetics, 2022)
Compression wood (CW) in gymnosperm brings great difficulties to wood industry using wood as raw materials since CW presents special wood structure and have different physical and chemical properties from those of normal wood (NW). Chinese fir (Cunninghamia lanceolata) is widely distributed in China. However, global transcriptome profiling of coding and long non-coding RNA in response to compression stress has not been reported in the gymnosperm species. In this study, we revealed that CW in Chinese fir exhibited distinct morphology and cytology properties compared with those of NW, including high lignin content, thick and round tracheid cells. Furthermore, we combined both PacBio long-read SMRT sequencing (Iso-Seq) and Illumina short-read RNA-Seq to reveal the transcriptome in stem-differentiating xylem (SDX) under different time points (2h, 26h, and 74h) upon compression stress in NW, CW, and OW (opposite wood), respectively. Iso-Seq was successfully assembled into 41,253 de-novo full-length transcriptome reference (average length 2,245 bp). Moreover, there were striking differences in expression upon compression stress, which were involved 13 and 7 key enzyme genes in the lignin and cellulose synthesis, respectively. Especially, we revealed 11 secondary growth-related transcription factors show differential expression under compression stress, which was further validated by qRT-PCR. Finally, the correlation between 6,533 differentially expressed coding genes and 372 differentially expressed long non-coding RNAs (lncRNAs) indicates that these lncRNAs may affect cell wall biogenesis and xyloglucan metabolism. In conclusion, our results provided comprehensive cytology properties and full-length transcriptome profiling of wood species upon compression stress. Especially we explored candidate genes, including both coding and long non-coding genes, and provided a theoretical basis for further research on the formation mechanism of CW in gymnosperm Chinese fir.